If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18-2(g+4)=(2g-6)
We move all terms to the left:
18-2(g+4)-((2g-6))=0
We multiply parentheses
-2g-((2g-6))-8+18=0
We calculate terms in parentheses: -((2g-6)), so:We add all the numbers together, and all the variables
(2g-6)
We get rid of parentheses
2g-6
Back to the equation:
-(2g-6)
-2g-(2g-6)+10=0
We get rid of parentheses
-2g-2g+6+10=0
We add all the numbers together, and all the variables
-4g+16=0
We move all terms containing g to the left, all other terms to the right
-4g=-16
g=-16/-4
g=+4
| y=51/2 | | .06x=0.72 | | -4(4y-10)-y=-3(y-3 | | x+5/3=5-x+4/4 | | 2(3x+2)×8x-5=14x+8 | | 0.12+0.06x=0.08 | | -5(4y-10)-y=3(y-5) | | 4/3x+1/2=5/6 | | x+7/18=2/9+x-3/4 | | 5(×-3)+4(x+3)=3(x-1) | | 2(9c-1)-14=16c+2 | | 1/4x+7/12=3/4 | | x+6/12=1/6+x-5/4 | | 3x+(2x+40)+(4x-40)=180 | | 3x+(2x+40)(4x-40)=180 | | -10(x+5)=76=-12-12 | | |11x+3|=6 | | 16(z+3)=4(z+9 | | 0=-16t^2+100 | | 5(2x-2)+2=10(1x-5)+42 | | 3(6x-3)=19 | | -(9x-4)-(2x-5)+10=-14(x-1)-(2x+13)+3 | | x3+8x+32=0 | | 5x-8+10x-53=180 | | 7r=16/2 | | 3(p+6)=-(2p+2) | | 8^(2x-2)=64 | | -2x(5x-7)+(3x+2)=4x-2(3+x) | | 16x-40+x=4x+10+8 | | 9/s=5/ | | X2=19x-88 | | 2(x+17)-4=16 |